Association of body roundness index with abdominal aortic calcification among middle aged and elderly population: findings from NHANES - Wu, Ji; Lu, Daojun; Chen, Xiang (Frontiers in Cardiovascular Medicine, 2024)
We aim to investigate the association between body round indexbody roundness index (BRI) and abdominal aortic calcification (AAC) among middle aged and elderly US residents. Methods: This cross-sectional study used data from the National Health and Nutrition Examination Survey (NHANES) 2013-2014 cycle, including 3,079 middle-aged and elderly participants aged 40 and above. Abdominal aortic calcification (AAC) scores for these participants were assessed using dual-energy X-ray absorptiometry (DXA).The Body Roundness Index (BRI) was calculated from participants' height and waist circumference, with all measurements conducted by trained surveyors using standardized methods. The relationship between BRI and AAC was analyzed using weighted multivariate logistic regression, adjusting for confounding variable.Additionally, restricted cubic splines (RCS) analysis was also employed to visualize the relationship between BRI and the risk of AAC.We found that those with AAC were significantly older and had a higher prevalence of smoking and chronic kidney disease (CKD) prevalence compared to those without AAC. Using weighted multivariable logistic regression, we determined that an increase of one unit in BRI was associated with a 22% higher risk of AAC.Additionally, higher BRI quartiles (Q2, Q3, Q4) showed significantly increased risks of AAC compared to the lowest quartile. Visualization using restricted cubic splines (RCS) indicated a gradual increase in AAC risk with higher BRI, which plateaued beyond a BRI of 7.2. This relationship was significant across different age and gender group.There is a positive association between abdominal obesity (as measured by BRI) and AAC in the middle-aged and elderly population. This suggests that attention should be paid to the impact of abdominal obesity on vascular health and that this factor should be considered in public health strategies.